2010
DOI: 10.31729/jnma.104
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic Assessment of Lateral Lamella of Cribiform Plate and Comparison of Depth of Olfactory Fossa

Abstract: INTRODUCTION: Endoscopic sinus surgery is an upcoming branch in rhinological practice but with some major risks since it has to play around the skull base area. Lateral lamella of cribriform plate is the thinnest area of the skull base. Thus this study is undertaken to evaluate the height of lateral lamella of cribriform plate and the depth of olfactory fossae by the help of computed tomographic images. METHODS: Computed tomographic study of 50 patients was done in Advanced Imaging and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
3
8
0
Order By: Relevance
“…This finding corroborated those reported elsewhere [14, 17, 2326]. We have found in the literature only one study [27], where type I was more frequent than type II, but it should be emphasized that their sample was the smallest (i.e., 50 MSCT examinations) among all the studies reviewed and also presented a prevalence of children with no balanced age distribution, which might have influenced the results. It should be also emphasized that our study used a sample of 174 CBCT examinations, which was quantitatively expressive compared to other studies, in order to investigate types of olfactory based on the Keros classification.…”
Section: Discussionsupporting
confidence: 91%
“…This finding corroborated those reported elsewhere [14, 17, 2326]. We have found in the literature only one study [27], where type I was more frequent than type II, but it should be emphasized that their sample was the smallest (i.e., 50 MSCT examinations) among all the studies reviewed and also presented a prevalence of children with no balanced age distribution, which might have influenced the results. It should be also emphasized that our study used a sample of 174 CBCT examinations, which was quantitatively expressive compared to other studies, in order to investigate types of olfactory based on the Keros classification.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike to Keros study [9], and similar studies [10,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31] our findings showed that Type I is the most common type (71.0%), followed by Type II (27.4%) and the Type III (1.6%) of the cases, respectively. However, our findings inline to results reported in studies from Philippine [16], USA [32], UK [33], Nepal [34], Malaysia [35], and Egypt [36] which confirms that the Keros type I is the most common. Moreover, two studies from UK [37] and UK [38] found that Keros type III was the most common.…”
Section: Discussionsupporting
confidence: 91%
“…Comparing the difference in olfactory fossa depth between both sides, it was found that the right side was more in-depth than the left side in 8 patients (> 1mm), and in a similar number of patients, the left side was more in-depth than the right side. Previous studies from Brazil [10], Turkey [19], India [28] [29], USA [32], and Nepal [34], showed that the right side was more in-depth than the left side with the percentages of 56.0%, 54.2%, 69.57%, 54.0%, 56.0% of asymmetric cases, respectively. The left side was deeper in other studies conducted in Malaysia [35],…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the height of LLCP on right side was 3.331+/-5.010mm, whereas on le side, it was 2.845+/-1.084mm.This differs from other studies as most of the 10,[12][13][14][15][16][17][18][19][20][21][22] studies had LLCP of >4mm.…”
Section: Discussionmentioning
confidence: 72%